Exhaust pollutants of traditional vehicles, their causes, effects, and ways to reduce them (Al-Farooq Journal of Sciences, 2026)
The problem of multi-form pollution and dangers is considered one of the current issues that occupies the minds of people, peoples and countries in our current time, which suffers from a state of escalating and dangerous environmental degradation that threatens living organisms and their future on the surface of the Earth. With the great industrial development, the number of vehicles invested, the increasing population growth, the extent of damage to the Earth’s protective ozone layer, and as a result of the high level of environmental pollution in crowded cities such as the city of Damascus as an example, it was necessary to monitor and measure this pollution and develop possible solutions that would mitigate it. The level of this pollution. The research began with a realistic study of one of the causes of pollution resulting from the exhaust gases of vehicles running with internal combustion engines. Experiments were conducted on a specific number of these vehicles and the level of pollution caused by these vehicles was tested in their natural condition. Then technical maintenance No. (2) was performed on them and the measurement was repeated again and the results were compared. We arrived at a set of precautionary measures and recommendations that must be taken to reduce this pollution, disseminate this experience and follow up on scientific research in this field with the aim of achieving a civilized and healthy environment. Suitable for future generations.